Comments on feature "Power Factor Correction and Power Quality Issues" on page 42-46 in Jurutera May 2007 - Cheng, Y. J., Dr. (The Institution of Engineers, Malaysia, 2012)
Link to publisher’s homepage at http://www.myiem.org.my/